1993
DOI: 10.1038/bjc.1993.474
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study of cystic fibrosis and malignancy

Abstract: On the basis of the present findings and previous case reports in the literature adenocarcinoma of the pancreas and adenocarcinoma of the terminal ileum may be associated with cystic fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 15 publications
2
42
0
2
Order By: Relevance
“…Also, there has been a concern about the risk of various cancers in CF patients and carriers of CFTR mutations (Malats et al, 2001). While a protective role of CFTR has been predicted for breast cancer and melanoma (Warren et al, 1991;Abraham et al, 1996), a significant excess of digestive tract cancer in CF patients has also been reported (Sheldon et al, 1993;Neglia et al, 1995). In the present study, we observed a reduced/negligible expression of CFTR in most (81%) pancreatic cancer cell lines, while it was expressed in cultured pancreatic ductal cells and normal pancreas ( Figure 1a).…”
Section: Discussionmentioning
confidence: 99%
“…Also, there has been a concern about the risk of various cancers in CF patients and carriers of CFTR mutations (Malats et al, 2001). While a protective role of CFTR has been predicted for breast cancer and melanoma (Warren et al, 1991;Abraham et al, 1996), a significant excess of digestive tract cancer in CF patients has also been reported (Sheldon et al, 1993;Neglia et al, 1995). In the present study, we observed a reduced/negligible expression of CFTR in most (81%) pancreatic cancer cell lines, while it was expressed in cultured pancreatic ductal cells and normal pancreas ( Figure 1a).…”
Section: Discussionmentioning
confidence: 99%
“…In 1993, Sheldon et al (21) reported a study among 412 subjects with CF and found two cases of pancreatic cancer [0.008 expected, P ϭ 0.001, odds ratio (OR) 61]. The increased incidence of digestive tract cancers, but not cancer in general, was then confirmed by Neglia et al (18) among 28,511 CF patients in the United States and Canada (risk ratio 6.5) and Europe (risk ratio 6.4).…”
Section: Cp Increases the Risk For Pancreatic Cancermentioning
confidence: 99%
“…Furthermore, intestinal transit is largely dependent on peristalsis (not ciliary activity), and may improve postnatally with compensatory changes in muscular tone or other physiological adaptations. Shortly after birth, the nonfunctional CFTR in CF significantly impairs airway mucociliary function in individuals who otherwise show normal humoral and cellular immunity with no evidence of increased susceptibility to viral infection or malignancy (Abraham et al, 1996;Dakin et al, 2002;Noah et al, 1997;Sheldon et al, 1993). Although tissue destruction and toxin production have long been viewed as characteristic traits of pseudomonal virulence, Pa is an environmentally ubiquitous saprophyte.…”
Section: Introductionmentioning
confidence: 99%